High Performance Structural Materials Proceedings of Chinese Materials Conference 2017 - Han, Yafang; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This proceedings volume gathers selected papers presented at the Chinese Materials Conference 2017 (CMC2017), held in Yinchuan City, Ningxia, China, on July 06-12, 2017. This book covers a wide range of powder metallurgy, high performance aluminum alloys, high performance titanium & titanium alloys, superalloys, metal matrix composite, space materials science and technology, rare metals, refractory metals and their applications, advanced ceramics materials, nanostructured metals and alloys. The Chinese Materials Conference (CMC) is the most important serial conference of the Chinese Materials Research Society (C-MRS) and has been held each year since the early 1990s. The 2017 installment included 37 Symposia covering four fields: Advances in energy and environmental materials; High performance structural materials; Fundamental research on materials; and Advanced functional materials. More than 5500 participants attended the congress, and the organizers received more than 700 technical papers. Based on the recommendations of symposium organizers and after peer reviewing, 490 papers have been included in the present proceedings, which showcase the latest original research results in the field of materials, achieved by more than 300 research groups at various universities and research institutes.
Preparation and Characterization of Fine 316L Stainless Steel Powders Prepared by Gas Atomization -- Synthesis of Beryllium Pebbles Using Plasma Rotating Electrode Process -- Effects of Internal Oxidation Methods on Microstructures and Properties of Al2O3 Dispersion-strengthened Copper Alloys.
Keywords: Building materials; Ceramic materials; Metals; Structural Materials; Building Materials; Ceramics; Metals and Alloys